2020
DOI: 10.1016/j.jjcc.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of evolocumab therapy on coronary fibrous cap thickness assessed by optical coherence tomography in patients with acute coronary syndrome

Abstract: Background: The addition of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, evolocumab, to statin therapy produced incremental regression of atherosclerotic plaques and a collaborative prevention of cardiovascular events in patients with coronary artery disease. The effect on fibrous-cup thickness, or extension of the atherosclerotic plaque with PCSK9-inhibitor, for several weeks after onset of acute coronary syndrome (ACS) has never been reported. Methods: This study aimed to examine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…Patients with low level of LDL-C who were treated with statins had a higher prevalence of calcification, which means that statins may help to prevent plaque rupture by calcification [ 45 ]. However, the addition of proprotein convertase subtilisin/kexin type 9 inhibitor to statin therapy might produce incremental growth in FCT and regression of the lipid-rich plaque after onset of ACS, thus decreasing the incidence of plaque rupture [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low level of LDL-C who were treated with statins had a higher prevalence of calcification, which means that statins may help to prevent plaque rupture by calcification [ 45 ]. However, the addition of proprotein convertase subtilisin/kexin type 9 inhibitor to statin therapy might produce incremental growth in FCT and regression of the lipid-rich plaque after onset of ACS, thus decreasing the incidence of plaque rupture [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…OCT imaging analysis, which provides a detailed image of ten times greater resolution than that achieved with IVUS, is the ideal imaging modality to assess the fibrous cap thickness of coronary plaque [16,22]. In a recent retrospective, observational OCT study revealed that compared to statin monotherapy, statin plus evolocumab provided a greater increase in fibrous-cap thickness of coronary plaques in patients with recent acute coronary syndrome [23]. The results of our study were consistent with the previous findings and we demonstrated a significant greater increase in minimum lumen area in the alirocumab arm assessed by OCT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PCSK9 inhibitors therapy added to statin therapy is capable of increasing fibrous cap thickening in acute coronary syndrome patients, reducing plaque vulnerability (82). However, the LDL-cholesterol lowering capacities of both PCSK9 inhibitors and statin treatment cannot solely explain the increased fibrous cap thickness suggesting that an unknown pleiotropic effect such as an anti-inflammatory effect independent of lowering LDLcholesterol may be involved (82).…”
Section: Pcsk9 Participates In Plaque Formationmentioning
confidence: 99%
“…In humans, PCSK9 inhibitors therapy added to statin therapy is capable of increasing fibrous cap thickening in acute coronary syndrome patients, reducing plaque vulnerability (82). However, the LDL-cholesterol lowering capacities of both PCSK9 inhibitors and statin treatment cannot solely explain the increased fibrous cap thickness suggesting that an unknown pleiotropic effect such as an anti-inflammatory effect independent of lowering LDLcholesterol may be involved (82). PCSK9 inhibitor treatment in an atherogenic mouse model increased the number of circulating endothelial progenitor cells and circulating angiogenic cells, markers of endothelial and vascular health associated with positive outcomes as reduced occurrence of cardiovascular events and death associated to cardiovascular causes (83).…”
Section: Pcsk9 Participates In Plaque Formationmentioning
confidence: 99%